2022
DOI: 10.1186/s12935-022-02576-0
|View full text |Cite
|
Sign up to set email alerts
|

LINC00662 enhances cell progression and stemness in breast cancer by MiR-144-3p/SOX2 axis

Abstract: Background Breast cancer (BC) is one of the most prevalent malignancies among women globally. Emerging evidence indicates that long non-coding RNAs (lncRNAs) are associated with BC carcinogenesis. In the current study, we explored the mechanism by which LINC00662 regulates BC. Methods Quantitative real-time PCR (qRT-PCR) assessed RNA expressions while western blot for protein levels. Kaplan Meier analysis evaluated overall survival (OS). Cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our results have also shown that LINC00662 overexpression promotes some stem-like traits in GBC cells, including an increase in CD133 + /CD44 + cell populations and the expression of stemness-associated genes such as OCT4 and NANOG , which is strongly associated with greater aggressiveness in cancer cells [ 11 , 22 , 23 ]. These findings were similar to those found in breast cancer cell lines, where LINC00662 knockdown decreased the expression of OCT4 and NANOG, which decreased invasion, proliferation, and tumor growth, suggesting that this lncRNA could actively participate in the acquisition of the stem-like phenotype in breast cancer [ 24 ]. Another characteristic closely attributable to lncRNAs is the development of chemoresistance [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results have also shown that LINC00662 overexpression promotes some stem-like traits in GBC cells, including an increase in CD133 + /CD44 + cell populations and the expression of stemness-associated genes such as OCT4 and NANOG , which is strongly associated with greater aggressiveness in cancer cells [ 11 , 22 , 23 ]. These findings were similar to those found in breast cancer cell lines, where LINC00662 knockdown decreased the expression of OCT4 and NANOG, which decreased invasion, proliferation, and tumor growth, suggesting that this lncRNA could actively participate in the acquisition of the stem-like phenotype in breast cancer [ 24 ]. Another characteristic closely attributable to lncRNAs is the development of chemoresistance [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, our in silico analyses showed that LINC00662 has two binding sites for miR-335-5p that could induce the repression of this miRNA, which was then confirmed in G-415 cells in which LINC00662 overexpression decreased miR-335-5p expression. Regarding this, similar studies showed that LINC00662 knockdown decreases the levels of OCT4 binding to miR-144-3p in breast cancer cells [ 24 ]. Since there were not significant differences in miR-335-5p levels between the control and LINC00662-transduced groups in GB-d1 cells, it is suggested that the oncogenic effects observed by LINC00662 overexpression could be through a different mechanism of regulation, which is very common among lncRNAs due to the large number of probable targets [ 40 ].…”
Section: Discussionmentioning
confidence: 93%
“…Such exo-lncRNAs have been implicated in the development, proliferation, invasion, angiogenesis, and drug resistance of tumors [ 10 ]. The LINC00662 gene, located on chromosome 19, encodes a 2085 bp lncRNA that is highly expressed in cancer, such as breast cancer and hepatocellular carcinoma [ 11 , 12 ]. Mechanistically, LINC00662 promotes tumor progression via interacting with both proteins and RNAs, as well as via regulating the Wnt/β-catenin, SMD and Hippo signaling pathways [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fuso et al [ 87 ] reported that miR-100-5p modulates the PlK1 gene and Wnt/β-catenin pathway, acting as a pro-differentiating agent in BCSC. MiR-144-3p and miR-145-5p target SOX2 in BC cells and are involved in cell migration, invasion, stemness, and cancer progression [ 88 , 89 ]. The hERG gene, which is related to cell proliferation, differentiation, and apoptosis in several types of cancers, including BC, is targeted by miR-362-3p [ 90 ].…”
Section: Circulating Mirnas As Indicators Of Clinical Response To Nat...mentioning
confidence: 99%